Design of Undershot Waterwheel Curved Blades as Picohydro Power Plant Generation in Tamangil Village - KristianusJamlay; Luther Sule; Duma Hasan (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) - ITP, 2016)
Utilization of hydropower plants picohydro recognized scale capable of meeting electricity demand, especially in areas not reached by the electricity such as rural areas. This study aims to analyze high waterfall (head), discharge and water resources available as well as the design of a water wheel undershot the current model corresponding curved blade. This research was conducted in the village of TamangilNuhuten the main object studied is the flow of the waterfall in the village. Primary and secondary data obtained through this study and Field and Library Research with stages such as the construction of drains, water discharge measurements, high measurement waterfall further analyzed quantitatively while the Library Research stages, namely the study of literature (book review). The results showed that the critical velocity water flow (v = 2.45 m/s), effectively head of waterfall (h = 2 m), the discharge of water used (Q = 0.0392 m3/s), and water power are utilized (Pair = 769.65 Watts). From the design obtained that rotation shaft (np = 78.08 rpm), tangential velocity (U = 2.45 m/s), the angular velocity of water wheel (ω = 8.1724 rad/s), the force on the water wheel (F = 96.18 N), torque at the wheels of water (T = 28.85 Nm), electric power that can be generated by a water wheel (Pwater wheel = 235.80 Watt), as well as maximum power efficiency obtained theoretical water wheel (ηteo = 30 59%) and the efficiency of water wheel axle (ηpra = 85.721%). Based on calculations assuming that there will be changes in water flow rate, it is known several important parameters including torque, mass flow rate, rotation, and power and maximum efficiency of water wheels is increasing. It was concluded that the flow of the waterfall village TamangilNuhuten potential to be used as a hydroelectric plant scale picohydro with water wheel underhot the current type and model of blade bent. Among torque, mass flow rate, rotation axis, and the water wheel power is proportional to the maximum efficiency. Hopefully, by the hydroelectric power plants pikohydro scale, it can meet the electricity needs of residents in the TamangilNuhuten village.